The commercial manager: the complete handbook for commercial directors and managers - Boyce, Tim; Lake, Cathy (Thorogood Publishing, 2007)
The Commercial Manager is the complete handbook for practitioners across all sectors of commerce and industry and covers every aspect of this multi-faceted role.